STRATEGI ADVOKASI TENAGANITA TERHADAP SIME DARBY PLANTATION DI MALAYSIA TAHUN 2020–2023 - Mumtaz Najih Fauzan; Fadhlan Nur Hakiem (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study examines how Tenaganita, a Malaysian local non-governmental organisation, deployed transnational advocacy network (TAN) strategies to compel the United States Customs and Border Protection (CBP) to issue a Withhold Release Order (WRO) against Sime Darby Plantation, the world’s largest producer of certified sustainable palm oil, between 2020 and 2023. Using a qualitative descriptive design based on documentary study, the research applies Keck and Sikkink’s framework of information, symbolic, leverage, and accountability politics, together with the boomerang pattern. The findings show that the forced-labour conditions at Sime Darby satisfied all eleven indicators defined by the International Labour Organization, while domestic enforcement and voluntary RSPO certification both failed. Tenaganita gathered grassroots evidence, transferred it to the Hong Kong-based NGO Liberty Shared for translation into a regulatory petition, and amplified it through investigative journalism that reframed a technical compliance issue as a global moral controversy. The integration of the four strategies converted moral pressure into a coercive sanction, culminating in roughly RM82 million in recruitment-fee reimbursement to more than 34,000 workers before the WRO was revoked in February 2023. Keywords: accountability politics; boomerang pattern; forced labour; transnational advocacy networks; withhold release order.   Abstrak: Studi ini mengkaji bagaimana Tenaganita, sebuah organisasi non-pemerintah lokal Malaysia, menerapkan strategi jaringan advokasi transnasional (TANs) untuk mendorong United States Customs and Border Protection (CBP) menerbitkan Withhold Release Order (WRO) terhadap Sime Darby Plantation, produsen minyak sawit berkelanjutan bersertifikat terbesar di dunia, pada 2020–2023. Dengan pendekatan kualitatif berdesain deskriptif berbasis studi dokumentasi, penelitian ini menerapkan kerangka Keck dan Sikkink tentang politik informasi, simbolis, leverage, dan akuntabilitas, beserta pola bumerang. Temuan menunjukkan bahwa kondisi kerja paksa di Sime Darby memenuhi seluruh sebelas indikator yang ditetapkan Organisasi Buruh Internasional, sementara penegakan hukum domestik dan sertifikasi sukarela RSPO sama-sama gagal. Tenaganita mengumpulkan bukti akar rumput, mentransfernya kepada LSM berbasis Hong Kong, Liberty Shared, untuk diterjemahkan menjadi petisi regulatif, dan memperbesarnya melalui jurnalisme investigatif yang membingkai ulang persoalan kepatuhan teknis menjadi kontroversi moral global. Integrasi keempat strategi tersebut mengonversi tekanan moral menjadi sanksi koersif, yang berpuncak pada pengembalian biaya perekrutan sekitar RM82 juta kepada lebih dari 34.000 pekerja sebelum WRO dicabut pada Februari 2023. Kata kunci: kerja paksa; politik akuntabilitas; pola bumerang; jaringan advokasi transnasional; withhold release order.